Tectonostratigraphic history of the Ediacaran-Silurian Nanhua foreland basin in South China - Yao, Weihua; Li, Zheng-Xiang (Elsevier BV, 2016)
This paper presents the tectonostratigraphic evolution of the Ediacaran-Silurian Nanhua Basin in South China and explores the relationship between clastic sedimentation in the basin and evolution of the adjacent Wuyi-Yunkai orogen. Sedimentary facies in the basin comprises, in an ascending order, turbiditic marine, shallow marine, and fluvial-dominated deltaic facies, featuring a lateral migration from southeast to northwest. We interpret the Ediacaran-Silurian Nanhua Basin as a foreland basin with a three-stage evolution history. Stage 1: the Ediacaran-Cambrian stage, recording the start of tectonic subsidence with turbiditic marine siliciclastic deposition, fed by exotic orogens outboard South China; Stage 2: the Ordovician to earliest-Silurian stage, characterized by a migrating depocenter with dominant shallow marine and deltaic siliciclastic deposition, fed by the local and northwestward propagating Wuyi-Yunkai orogen; Stage 3: the Silurian stage, showing the arrival of depocenter in the Yangtze Block during the waning stage of the orogeny with deltaic deposition in the remanent foreland basin. The Wuyi-Yunkai orogen remained the dominant sedimentary source region during Stage 3. Stage 1 was likely related to the collision of the South China Block toward northern India during the assembly of Gondwana, whereas Stages 2 and 3 recorded sedimentation during the northwestward propagation and subsequent orogenic root delamination/collapse of the Wuyi-Yunkai orogen, respectively. The Wuyi-Yunkai orogeny in South China is interpreted to have resulted from the far-field stress of the collision between South China and Indian Gondwana.